Effects of different geriatric nursing teaching methods on nursing students' knowledge and attitude: Systematic review and network meta-analysis. - Yifen Cheng; Shuqin Sun; Yu Hu; Jing Wang; Wenzhen Chen; Yukuan Miao; Hui Wang (PLoS ONE)
Objective The purpose of this study was to evaluate the effect of different teaching methods of geriatric nursing on the mastery of geriatric knowledge among nursing students and their attitude toward the elderly. Methods Relevant randomized controlled trials (RCTs) and quasi-experimental studies on teaching methods to improve nursing students' knowledge and attitude were systematically retrieved in electronic databases. The time scale of retrieval spans from the database establishment to January 2024, and the database consists of PubMed, the Cochrane Library, Web of Science, Embase, China National Knowledge Infrastructure Database (CNKI), China Biological literature database (CBM), Wanfang Database and VIP Database. Network meta-analysis was performed by Stata 16.0 software. Results Thirty-nine studies involving 5310 nursing students met our inclusion criteria, and a total of 6 teaching methods were analyzed. According to the surface under the cumulative ranking (SUCRA) ranking, problem-based learning (PBL) was most effective in enhancing the knowledge mastery of geriatric nursing, while simulation-based learning (SBL) demonstrated the best application effect in improving nursing students' attitude toward the elderly. When considering both knowledge acquisition and attitude improvement simultaneously, service learning combined with traditional teaching method (SL+TTM) was found to exhibit the most optimal effectiveness. Conclusion Educators in geriatric nursing education should prioritize the adoption of PBL, SBL and SL + TTM to enhance nursing students' knowledge and attitude. Protocol registry PROSPERO (CRD42023442001).